Analisis Sinyal Wireless Berdasarkan Jarak Antar Access Point Menggunakan Metode Simulated Annealing Pada SMAN 1 Praya Tengah - MUHAMMAD FAUZI ZULKARNAEN; Moh Husni Taufik; Maemun Saleh (LPPM STMIK Lombok, 2018)
Access point placement on wireless networks is needed to optimize the strength of signal received by receiver from transmitter. The most influential parameter in determining the performance of access point position is signal strenght, because this value will be used to determine the coverage area of a access point. In this research, signal strengths of access point to receiver in the SMAN 1 Praya Tengah have been measured using inSSIDer application and results in the values of RSSI from transmitter to receiver. Data obtained from the filed measurements are used to analyse the influence of access point placement using simulate annealing. The research conducted is expected to generate an appropriate position and analysis for further optimization of access point position on wireless network.